PENGARUH KOMPETENSI DAN KESEJAHTERAAN TERHADAP KINERJA KARYAWAN APOTEK DI KOTA MAGELANG: Dispensary,Competence,Welfare, Employee Performance - Pratama, Arfananda Dias; Giovanni, Axel (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2021)
This study examined the influence of competence and well-being on the productivity of pharmaceutical personnel in the city of Magelang. This research uses a quantitative approach. The study used primary data from 100 respondents as a sample selected by a simple random sampling method. The collected data is analyzed through multiple linear regression analysis using SPSS. Research shows that competence and well-being simultaneously affect employee performance. Competence has a positive and significant effect on employee productivity, while well-being has a positive but insignificant effect on employee performance. The results of the study provide management implications for the welfare of Magerland City Pharmacy by developing employee welfare program policies to increase productivity. We want the pharmacies we operate to thrive and sustainably with increased productivity.